The epidemiology of sport-related concussion - Daneshvar, D. H.; Nowinski, C. J.; McKee, A. C.; Cantu, R. C. (Clinics in Sports Medicine, 2011)
Concussions and head injuries may never be completely eliminated from sports. However, with better data comes an improved understanding of the types of actions and activities that typically result in concussions. With this knowledge can come improved techniques and rule changes to minimize the rate and severity of concussions in sports. This article identifies the factors that affect concussion rate.